Third-Day Oxygenation Index is an Excellent Predictor of Survival in Children Mechanically Ventilated for Acute Respiratory Distress Syndrome - Rsovac S; Milošević K; Plavec D; Todorović D; Šćepanović L (Dove Medical Press, 2020)
Snežana Rsovac,1 Katarina Milošević,1 Davor Plavec,2,3 Dušan Todorović,4 Ljiljana Šćepanović4 1Department of Pediatric and Neonatal Intensive Care, University Children’s Hospital “Tiršova”, Faculty of Medicine, University of Belgrade, Belgrade, Serbia; 2Srebrnjak Children’s Hospital, Zagreb, Croatia; 3Medical Faculty Osijek, JJ Strossmayer University of Osijek, Osijek, Croatia; 4Institute of Medical Physiology “Richard Burian”, Faculty of Medicine, University of Belgrade, Belgrade, SerbiaCorrespondence: Dušan Todorović Tel +381642739534Email t.dusan@hotmail.comPurpose: The aim of this study was to assess the association between oxygenation index (OI) and outcome in children with acute respiratory distress syndrome (ARDS).Patients and Methods: Patients (age, > 30 days) in the pediatric intensive care unit from April 2011 to March 2016 with ARDS and who were mechanically ventilated were included. Patients were divided into two age groups: infants (< 12month) and older children. Lowest PaO2/FiO2 and SpO2/FiO2 ratios and highest mean airway pressure (MAP) were recorded on the ﬁrst day of ARDS and after 72 h. OI was calculated on the first and third days of mechanical ventilation (MV) and its association with OI (first and third days) and short-term mortality evaluated at 28 days.Results: MV was initiated a mean of 2.3 days after admission (median, 1.0 day; maximum 14 days). The average MV duration for all patients was 11.8 (median, 7.0) days. Mean (95% confidence interval (CI)) OI values on the first day of MV were 14.17 (11.94– 16.41), 12.72 (10.68– 14.75), and 13.24 (11.73– 14.74) for infants, older children, and all participants, respectively. In survivors (n=39) mean OI was 11.66 (9.64– 13.68) compared with 15.22 (13.03– 17.40) in non-survivors (n=31). Logistic regression analysis revealed that OI on day 3 had highly significant prognostic value for mortality (odds ratio, 256.5, 95% CI 27.1– 2424, p< 0.001), with an AUC of 0.919 (cut-off value, 17; positive predictive value, 0.905; negative predictive value, 0.964; p=0.0001). In contrast, OI on day 1 did not have significant prognostic value (AUC, 0.634; p=0.056) for short-term mortality. Different modes of MV were not significantly associated with outcome (p> 0.05).Conclusion: OI is a simple, highly accurate, and sensitive predictor of the survival (short-term mortality) of children mechanically ventilated for ARDS.Keywords: mortality, respiration, artificial, prognosis, intensive care units, pediatric, blood gas analysis, survivors mortality of children mechanically ventilated for ARDS